Cytoglobin promotes sensitivity to ferroptosis by regulating p53‐YAP1 axis in colon cancer cells. Issue 7 (21st February 2021) - Ye, Shazhou; Xu, Mingjun; Zhu, Tingwei; Chen, Jiayi; Shi, Shanping; Jiang, Haizhong; Zheng, Qingfang; Liao, Qi; Ding, Xiaoyun; Xi, Yang
Abstract: Ferroptosis is an iron‐dependent mode of non‐apoptotic cell death characterized by accumulation of lipid reactive oxygen species (ROS). As a regulator of ROS, cytoglobin (CYGB) plays an important role in oxygen homeostasis and acts as a tumour suppressor. However, the mechanism by which CYGB regulates cell death is largely unknown. Here, we show that CYGB overexpression increased ROS accumulation and disrupted mitochondrial function as determined by the oxygen consumption rate and membrane potential. Importantly, ferroptotic features with accumulated lipid ROS and malondialdehyde were observed in CYGB‐overexpressing colorectal cancer cells. Moreover, CYGB significantly increased the sensitivity of cancer cells to RSL3‐ and erastin‐induced ferroptotic cell death. Mechanically, both YAP1 and p53 were significantly increased based on the RNA sequencing. The knock‐down of YAP1 alleviated production of lipid ROS and sensitivity to ferroptosis in CYGB overexpressed cells. Furthermore, YAP1 was identified to be inhibited by p53 knock‐down. Finally, high expression level of CYGB had the close correlation with key genes YAP1 and ACSL4 in ferroptosis pathway in colon cancer based on analysis from TCGA data. Collectively, our results demonstrated a novel tumour suppressor role of CYGB through p53‐YAP1 axis in regulating ferroptosis and suggested a potential therapeutic approach for colon cancer.